Investigation of acid exposure duration on migration behavior of sodium borosilicate glass-ceramic coatings - Copoglu, Nurullah; Ceylan, Iremnur; Karaahmet, Oguz; Cicek, Bugra (ELSEVIER, 2024)
This study investigates the migration behavior of Na2O-B2O3-SiO2 glass-ceramic coatings under different exposure durations. Sinter-crystallization at 830 degrees C for 4.5 min transforms the glass into a crystalline phase. Coatings were immersed in 3% acetic acid solutions for durations ranging from 15 to 960 min. Chemical migration was measured using ICP-MS analysis, while SEM and surface profilometry assessed surface morphology and roughness. Coatings remained compliant with ISO 4531:2022 food-contact standard, even after 960 min. Dissolution of alkaline network modifiers initially increased roughness, which then returned to the initial value. This research provides insights into the stability and applicability of glass-ceramic coatings for long-term use in food-contact surfaces, contributing to the field of surface coatings and food safety.
Keywords: Food contact articles; Coating; Glass-ceramic; Migration; Metal release; ZRO2; Chemistry; Materials Science; Physics